2018
DOI: 10.3390/coatings8060225
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion at Room Temperature in Cu-Ni(Fe) Nanolaminates

Abstract: Abstract:The decomposition of a one-dimensional composition wave in Cu-Ni(Fe) nanolaminate structures is quantified using X-ray diffraction to assess kinetics of the interdiffusion process for samples aged at room temperature for 30 years. Definitive evidence for growth to the composition modulation within the chemical spinodal is found through measurement of a negative interdiffusivity for each of sixteen different nanolaminate samples over a composition wavelength range of 2.1-10.6 nm. A diffusivity valueĎ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As it has been known, the molecule diffusion effect induces bonding at a contact interface. Certain metals also can have the interfacial diffusion effect when they are in contact [42,43]. The nano scale diagram of an inter-diffusion is illustrated in Fig.…”
Section: The Friction Force Considering the Rebinding Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…As it has been known, the molecule diffusion effect induces bonding at a contact interface. Certain metals also can have the interfacial diffusion effect when they are in contact [42,43]. The nano scale diagram of an inter-diffusion is illustrated in Fig.…”
Section: The Friction Force Considering the Rebinding Effectmentioning
confidence: 99%
“…The multi-layer structure combined with thin films of copper (Cu)/magnetic materials (Co, NiFe)/Si has been widely used in the application of nanodevices [39,40]. The diffusion of copper into other materials has been considerably www.Springer.com/journal/40544 | Friction studied [41][42][43]. Liu [42] found that atoms diffused at the interface when two Cu films are brought into contact, causing grain growth, also known as diffusion bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation